Mixed Methods of Learning in Schools: Reshaping comprehensive education in Synchronous and Asynchronus - Riska Lastari; Lismawati; Heru Wibowo; Totong Heri (Jurnal Pendidikan Islam, 2023)
This research was conducted to determine whether there is influence of the Synchronous and Asynchronous approach methods on student learning outcomes. This research was conducted at SMAN 3 Tangerang. The population in this study were 310 students and 175 students were taken as a sample. This research is a quantitative research and uses a questionnaire in collecting data. The results of the questionnaire data were processed using the IMB SPSS Statistics application version 25. The results of this study indicate that there is a positive influence in online learning using the Synchronous and Asynchronous approach methods on student learning outcomes. Even though the magnitude of this influence, based on the results of the analysis the coefficient of Determination (R2) is relativaly low, namely 0.292 or 29.2 %.